RANCANG BANGUN SISTEM INFORMASI KEPEGAWAIAN BERBASIS WEB PADA PT SRI INDAH MANDIRI - Carlos, Carlos daniel; Ridho, Muhammat Rasid (LPPM Universitas Putera Batam, 2023)
Today's technology has developed rapidly. This can be seen from the many uses of technology in everyday human life. PT Sri Indah Mandiri is a company that has been established since 1997 which is engaged in manufacturing to provide building materials. So far, the administrative recording process for the presence of PT Sri Indah Mandiri still relies on the application of Ms. Excel and printed documents resulting in an increasing number of accumulations of attendance data and searching for data takes quite a long time. In addition, the calculation of overtime is still done manually, so it often causes errors in the process of calculating employee overtime. This study aims to design a staffing information system at PT Sri Indah Mandiri to improve and facilitate the process of recording attendance at PT Sri Indah Mandiri. The system development method used is the Agile Scrum SDLC method. The results of the system design show that the system improves and facilitates the process of recording attendance so that it can make PT Sri Indah Mandiri operate more effectively and efficiently in its business activities.